STUDI TENTANG ANOPHELES DAN FAKTOR RISIKO KEJADIAN MALARIA DI KECAMATAN PASAK TALAWANG KABUPATEN KAPUAS KALIMANTAN TENGAH TAHUN 2015 - INDRIA AUGUSTINA PROGRAM, NIM011314153009 (2017)
This study aims to analyze the risk factors associated with the incidence of malaria at primary school age children in the Pasak Talawang subdistric, Kapuas regency, Central Kalimantan. This type of research is an analytic observational study with cross sectional design. The population in this study are all children of primary school age in the Pasak Talawang subdistric. The sample size of this study as many as 139 samples. The risk factors studied were age, sex, use of mosquito nets at night, a habit of activity outside the home at night, the presence of breeding places of mosquitoes, house building, house walls, floor houses, roofs and ventilation of the house. The statistical test used was bivariate logistic regression (α = 0,05) to analyze or not there is a significant relationship between malaria incidence and risk factors followed by multivariate logistic regression test (α = 0,05). The results of risk factors that have a relationship with the incidence of malaria at primary school age children in the Pasak Talawang subdistric are the presence of home ventilation (p = 0.044; PR = 8.432; CI = 1.063 to 66.865), roofs (p = 0.020; PR = 4.902; CI = 1.286 to 18.690) and the existence of breeding places (p = 0.003; PR = 6.183; CI = 1.880 to 20.336). Microscopic examination found that 13 respondents infected with P. falciparum. An. subpictus breeding places found in freshwater that are ditches and ponds where located in the Jangkang Village and Dandang Village. The conclusions of the study are risk factors that have a relationship with the incidence of malaria at primary school age children in the Pasak Talawang subdistric, Kapuas regency are home ventilation, roofs and breeding places. The prevalence of malaria at primary school age children in the Pasak Talawang subdistrict, Kapuas regency, Central Kalimantan Province amounted to 9.35% infected by P. falciparum. Examination of the species Anopheles larvae obtained An. subpictus.